PENGARUH PENGETAHUAN KURIKULUM 2013 TERHADAP KOMPETENSI PROFESIONALISME GURU KELAS SD/MI SE-KECAMATAN SINJAI BARAT - Selfiana; Muhammad Yahdi; Nursalam (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of 2013 curriculum knowledge on theprofessional competence of SD / MI class teachers in West Sinjai District. This studyinvolved two variables, namely the independent variable, namely 2013 curriculumknowledge, while the dependent variable was teacher professional competence. Thisquantitative research uses ex-post facto research and a simple linear regression researchdesign. The population in this study were all SD / MI class teachers in the West SinjaiDistrict totaling 180 people. While the sample in this study were 36 people using clustersampling technique. The instruments used in this study were questionnaires anddocumentation. The data analysis technique used is descriptive statistics and inferentialstatistics. The results of the research from descriptive statistics obtained that the averagevalue of the 2013 curriculum knowledge for SD / MI class teachers in West SinjaiDistrict was in the moderate category, namely 72.22%, while the results of theprofessional competence of SD / MI class teachers in West Sinjai District were atmedium category, namely 52.78% and inferential statistics obtained (tcount) = 18.848while (ttable) = 2.032 for a significance level of 0.05%. Because tcount is greater thanttable, it can be concluded that H0 is rejected and H1 is accepted, so it is said that 2013curriculum knowledge has an effect